Design, Fabrication and Testing of Gravity-Powered Light - Giri, Sushant Raj; Lakhemaru, Prashant; Shrestha, Anil; Lama, Sanjeev; Sapkota, Shuveksha (Journal of the Institute of Engineering, 2020)
With every passing day, the need for sustainable living on Earth is increasing greatly. For this world needs to start using renewable energy resources. The following project shows how electricity can be generated using gravity in simplest possible way. Mechanical components like Spur gears, chain and mass provide input to an electrical circuit through a generator motor. Every time you lift the weight, gravitational potential energy is converted into electrical energy for 12 seconds in this model. The power generation from gravity is cheaper and bio-efficient as compared to solar and other renewable energy sources. In recent times due to effects of pollution and global warming there is a need for generating power from renewable sources. The reason for generating power using gravity is that it is available all over the Earth, abundant and consistent too. In this project, the gravitational energy of a heavy particle is converted to the electrical energy. When the heavy particle falls down from a higher altitude to a lower one, its potential energy is converted into the kinetic energy. Then this energy is converted to electricity by using a synchronous motor. With the increasing of the altitude of the load, the lighting time increases. If load increases, power production also increases, but the lighting time decreases.